A reassessment of the fish-salting workshops 1 and 2 of Tróia (Portugal): The ceramic contexts - Vaz Pinto, Inês; Magalhães, Ana Patrícia; Brum, Patrícia (Rei Cretariae Romanae Fautorum Acta, 2022)
Archaeological work carried out in the large factory that includes Workshops 1 and 2, on the site of Tróia, between 2007 and 2010, brings new evidence to the general chronological framework that was established by the consistent work of R. Étienne, Y. Makaroun and F. Mayet published in 1994 in the monograph Un Grand Complexe Industriel à Tróia (Portugal). Several new stratigraphic contexts confirm and give more substance to the three phases identified and allow the foundation of this factory and its abandonment to be dated slightly earlier. This article will briefly present the ceramics of these contexts, some of them already published, as a reassessment of the phasing and dating of these workshops, which for now generally date the production of this important fish-salting center.